Place of Enunciation and Poetic Procedures in “España, aparta de mí este caliz” [“Spain, take this cup away from me”] by César Vallejo - Guáqueta Rocha, Edson Steven (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article aims at examining the context or place of enunciation of the poem “España, aparta de mí este caliz”[“Spain, take this cup away from me”] (1939) by the Peruvian poet César Vallejo, as well as analyzing some of his poetic procedures, particularly the appropriation made by the author of the rhetoric of Christianity. The study explores this poet ́s identification with Spain, specifically with the Republican faction, during the Spanish Civil War (1936-1939); an experience from which the writing of this poem emerged. We also analyze the universality of this poem, whose meaning transcends the geographical frontiers of Spain, and the historical context of the conflict during which it was written, taking root in the will to harmonize Christianity and Marxism –movement to whichthe author was politically committed, both in Spain, and in his native Peru– through the ideal of redemption of the dispossessed. With this purpose, the present study describes the creative, subversive use made by Vallejo of expressions of biblical origin throughout this poem, such as the use of Catholic prayers that were and continue to be part of the cultural background of many of his readers